2020
DOI: 10.3233/ves-200697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vocal changes after vestibular rehabilitation in patients with balance disorders

Abstract: BACKGROUND: Although there are articles and studies that associate postural changes with changes in vocal quality, to the best of our knowledge, this was the first study investigating the association between balance disorders and voice. OBJECTIVE: This study aimed to determine whether patients with balance disorders present any clinical, acoustic, or endoscopic vocal changes, and if the correction of balance impairments, such as through vestibular rehabilitation, lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Our results are in agreement with those of Bruno et al 4 and Caçador et al 6 , 20 who showed that posturographic values in dysphonic patients at baseline were within normal ranges. On the contrary, Nacci et al 5 and Lobryeau-Desnus et al 9 found postural alterations in baseline conditions with a significant improvement in the stabilometric parameters after speech rehabilitation.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in agreement with those of Bruno et al 4 and Caçador et al 6 , 20 who showed that posturographic values in dysphonic patients at baseline were within normal ranges. On the contrary, Nacci et al 5 and Lobryeau-Desnus et al 9 found postural alterations in baseline conditions with a significant improvement in the stabilometric parameters after speech rehabilitation.…”
Section: Discussionsupporting
confidence: 94%
“…Our results after therapy with the vestibular instrumental technique for rehabilitation are also in agreement with Caçador et al 20 , who investigated the association between voice and balance disorders. The study analysed vocal differences (clinical, video-endostroboscopic, audio-perceptual and acoustic vocal parameters) in patients with vestibular dysfunction treated with vestibular rehabilitation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was related to an improvement in vocal parameters found by the patients with the VHI. In a study not included in this review, the authors improved the quality of the voice indirectly [ 47 ]. They did it with a treatment for balance disorders that improved posture [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study not included in this review, the authors improved the quality of the voice indirectly [ 47 ]. They did it with a treatment for balance disorders that improved posture [ 47 ]. This highlights the importance of a postural treatment to act, indirectly, to the voice.…”
Section: Discussionmentioning
confidence: 99%